2022
DOI: 10.1021/acssensors.2c01926
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric Surface-Selective Regulation of Au/In2O3 Nanofibers as an Exhaled H2S Chemiresistor for Periodontitis Diagnosis

Abstract: As one of the most prevalent diseases in the world, timely early intervention for periodontitis is a great challenge because the indicator is imperceptible. The exhaled H2S is considered to be a promising biomarker for fast and invasive periodontitis screening; however, the high-performance H2S gas sensor with excellent selectivity and sensitivity which is applicable to the oral cavity remains technically challenging. Herein, a self-assembled monolayer (SAM)-functionalized Au/In2O3 nanofiber (NF) sensor for H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…Encouraged by the ultralow response concentration toward H 2 S and excellent anti-interference ability of the as-proposed TCN, we measured the oral H 2 S levels of healthy volunteers before and after brushing. As shown in Figure e, the average response of the as-proposed sensing device to morning exhalation (the tester did not brush the teeth) was recorded as 2.7 under UV-light irradiation, corresponding to 75 ppb H 2 S. This value is consistent with the previously reported physiological halitosis (morning halitosis) . Notably, the concentration of H 2 S in the oral cavity decreased substantially after brushing.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Encouraged by the ultralow response concentration toward H 2 S and excellent anti-interference ability of the as-proposed TCN, we measured the oral H 2 S levels of healthy volunteers before and after brushing. As shown in Figure e, the average response of the as-proposed sensing device to morning exhalation (the tester did not brush the teeth) was recorded as 2.7 under UV-light irradiation, corresponding to 75 ppb H 2 S. This value is consistent with the previously reported physiological halitosis (morning halitosis) . Notably, the concentration of H 2 S in the oral cavity decreased substantially after brushing.…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure 3e, the average response of the as-proposed sensing device to morning exhalation (the tester did not brush the teeth) was recorded as 2.7 under UV-light irradiation, corresponding to 75 ppb H 2 S. This value is consistent with the previously reported physiological halitosis (morning halitosis). 35 Notably, the concentration of H 2 S in the oral cavity decreased substantially after brushing. There was only a slight fluctuation of the H 2 S level in the oral cavity 12 h after brushing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CuO nanoparticle-coated TiO 2 nanochannels were reported by Song et al as a remarkably sensitive sensor for detecting H 2 S . In the same way, Xu et al applied Au modified In 2 O 3 nanofiber sensor for H 2 S detection . Gao et al reported a WO 3 nanoplate MOS sensor with significantly higher selectivity for cyclohexene than for other VOCs, such as benzene, ethanol, and acetone …”
Section: Metal Oxide Semiconductorsmentioning
confidence: 98%
“…68 CuO nanoparticle-coated TiO 2 nanochannels were reported by Song et al as a remarkably sensitive sensor for detecting H 2 S. 69 In the same way, Xu et al applied Au modified In 2 O 3 nanofiber sensor for H 2 S detection. 70 Gao et al reported a WO 3 nanoplate MOS sensor with significantly higher selectivity for cyclohexene than for other VOCs, such as benzene, ethanol, and acetone. 71 It is worth noting that polyoxometalates (POMs) and colloidal quantum dots (CQDs) have been investigated as sensing materials to improve the selectivity and sensitivity of MOSs.…”
Section: ■ Metal Oxide Semiconductorsmentioning
confidence: 99%